2017
DOI: 10.18632/oncotarget.20719
|View full text |Cite
|
Sign up to set email alerts
|

Isobaric tags for relative and absolute quantification-based proteomic analysis of testis biopsies in rhesus monkeys treated with transient scrotal hyperthermia

Abstract: This study aimed to examine the cellular and molecular events that occur in rhesus monkey testes after scrotal hyperthermia. Eight male adult rhesus monkeys were subjected to scrotal hyperthermia at 43°C for 30 min daily for 6 consecutive days. Sperm concentration, reproductive hormones, and testis histology were examined before hyperthermia (day 0), and at 8, 15, 30, 45, 60, 75, and 90 days after the initiation of hyperthermia. iTRAQ-based proteomic analysis was conducted on testicular tissues collected on da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
(50 reference statements)
0
3
2
Order By: Relevance
“…Our results revealed that during the pre‐experimental period, all subjects exhibited cortisol, FSH, and estradiol levels below the normal range. In Cynomolgus monkeys, the typical concentrations of cortisol, FSH, and estradiol in the bloodstream exceed 40, 8, and 30 pg/mL, respectively 35–37 . However, in the present study, these values remained below 3, 4, and 3 pg/mL throughout the experimental period.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Our results revealed that during the pre‐experimental period, all subjects exhibited cortisol, FSH, and estradiol levels below the normal range. In Cynomolgus monkeys, the typical concentrations of cortisol, FSH, and estradiol in the bloodstream exceed 40, 8, and 30 pg/mL, respectively 35–37 . However, in the present study, these values remained below 3, 4, and 3 pg/mL throughout the experimental period.…”
Section: Discussioncontrasting
confidence: 65%
“…In Cynomolgus monkeys, the typical concentrations of cortisol, FSH, and estradiol in the bloodstream exceed 40, 8, and 30 pg/mL, respectively. [35][36][37] However, in the present study, these values remained below 3, 4, and 3 pg/mL throughout the experimental period. Elevations in cortisol levels are typically anticipated in response to exposure to stress.…”
Section: F I G U R Econtrasting
confidence: 68%
“…In the CIRBP knockout mouse model (Masuda et al ., ), the number of undifferentiated spermatogonia was significantly reduced, and spermatogenesis was also damaged. In a previous study, we found that CIRBP expression after heat shock was significantly decreased in the testes of monkeys (Rao et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In our previous study, we used proteomics to identify differentially expressed proteins in monkey testes after transient scrotal hyperthermia (43 °C) for 30 min daily for six consecutive days (Rao et al ., ). We found that the expression of the cold‐inducible RNA‐binding protein (CIRBP) was downregulated 0.58‐fold eight days post‐treatment compared to the pre‐treatment level (Rao et al ., ). A compelling study shed light on post‐transcriptional regulation required for circadian orchestration of the clock network.…”
Section: Introductionmentioning
confidence: 97%
“…In rams HSP70 has been found to be differentially expressed in SP after SI (Rocha et al, 2015), and a study in rabbits also identified HSP70 along with other heat stress proteins, to be increased in epididymal fluid after a chronic exposure to high temperature and humidity (Pei, Wu, & Qin, 2012). Similarly monkeys exposed to transient scrotal hyperthermia have been shown to have differentially expressed proteins at the early stage of damage, relating to the spliceosome pathway, including heat shock‐related 70 kDa protein 2 (Rao et al, 2017). The protein is emitted as a response to cellular stress and the elevated expression is likely due to its protective roles in repairing the damage caused by heat stress (Pei et al, 2012).…”
Section: Discussionmentioning
confidence: 99%